Biotechnology in Agriculture and Food Processing Opportunities and Challenges - Panesar, Parmjit Singh;Ed. Marwaha, Satwinder S;Ed (CRC Press, Taylor & Francis, 2014)
"An instructive and comprehensive overview of the use of biotechnology in various agriculture and food applications, this book discusses the current status of applications for improving quality and productivity of agriculture and food products. It discusses plant tissue culture techniques, genetic engineering in food ingredient production, bio-fertilizers, bio-pesticides, enzymes, genetically modified foods etc.